Alguém com quem contar: emancipação humana e organizações museais - Castro, Diana Costa de (2016)
The subject of this research is the new museums created to compose the development processes in the cities. Starting from a theoretical essay I created a substantiation to analyse the human emancipation in museums since a Paulo Freire´s perspective. I propose the Boundary Zone thesis as well that such organizations could contribute to the society´s development emancipation. After this I have made a research with questionnaires, interviews and local observation. The data analysis, since a dialectical perspective, search for contradictions and synthesis. The questionnaires were organized with descriptive statistics and analysed together with the data from interviews and observation qualitatively. The other interviews were analysed from a critical discourse analysis perspective. From the result I consider that in such organization prevails a substantive rationality. This organizations finality includes a qualified leisure and the education through the culture and, as well, sociability possibilities even if restricted to people who knows each other, beyond their usual functions as keeper, research, maintenance and collections exhibitions. The exhibitions contents seems to be almost irrelevant to education from the visitors perspective, though it has a crescent visibility since an instrumental rationality. Despite this I prove that the museum can have an active role in the human emancipation, especially in the subcategories related to a society critical perception and utopia. An empirical perception shows us a Boundary Zone as an important component in the new museums, as well as their exhibitions area. Both in the Boundary Zone and the exhibitions exists some influence in the visitors transformation and emancipation. Such substantive organizations play an incisive role in the society and work as agents with whom people can trust in the emancipatory process, depending of their administration.